Psychological distress in elite adolescent soccer players following deselection - Blakelock, D. J.; Chen, M. A.; Prescott, T. (Journal of Clinical Sport Psychology, 2016)
Elite adolescent soccer players may represent one athletic population that is vulnerable to developing psychological distress following deselection. This study examined the proportion of players experiencing clinical levels of psychological distress following selection procedures and whether player status (i.e., deselected vs. retained) had a significant effect on psychological distress. Data was collected from 91 players who completed the General Health Questionnaire -12 at three time points: 7-14 days before selection procedures, 7 days after and 21 days after. Although outcomes were heterogeneous, a sizable proportion of deselected players were found to experience clinical levels of psychological distress. A factorial ANOVA (p < .001) found that deselected players experienced higher levels of psychological distress than retained players at postselection time points. The research provides evidence that some deselected players are "at risk" of developing clinical levels of psychological distress. Clinical implications and recommendations for future research are discussed. ABSTRACT FROM AUTHOR